Mining operation along Nome beach, Alaska, 1900 - Hester, Wilhelm, 1872-1947 (1898)
Written on verso: Working along Nome Beach. PH Coll 318.1053 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number